2016
DOI: 10.1186/s12955-016-0420-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic Fatty Liver Disease (NAFLD) is associated with impairment of Health Related Quality of Life (HRQOL)

Abstract: BackgroundNAFLD impacts patient reported outcomes (PROs). Our aim was to assess the impact of NAFLD on patients’ HRQOL.MethodsNational Health and Nutrition Examination Survey (NHANES) 2001–2011 data were used to identify adult patients with NAFLD [Fatty Liver Index (FLI) > 60 in absence of other liver disease and excessive alcohol >20 g/day for men, >10 g/day for women]. Patients with other chronic diseases (ex. HIV, cancer, end-stage kidney disease) were excluded. Subjects without any of these conditions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 20 publications
6
107
1
3
Order By: Relevance
“…Our study indicates impairment of HRQOL among patients with suspected NASH that is comparable with previous reports [21,22]. In their studies, Golabi et al [23] and Sarrafzadegan et al [24] illustrated a noticeable QOL impairment in NAFLD [23,24].…”
Section: Discussionsupporting
confidence: 90%
“…Our study indicates impairment of HRQOL among patients with suspected NASH that is comparable with previous reports [21,22]. In their studies, Golabi et al [23] and Sarrafzadegan et al [24] illustrated a noticeable QOL impairment in NAFLD [23,24].…”
Section: Discussionsupporting
confidence: 90%
“…The important most recent reviews appropriately address benefits of healthy diet and exercise on NAFLD[27] both in adults[28] and in children[29], even if other factors, genetic[30], behavioural and environmental should not be neglected[31,32]. The opportunity for the medicine are relevant since articulated clinical intervention, which, according to our results, are justified, can be pursued with a focus on nutritional profile, physical exercise mainly open-air for enhancing sun exposure and improving sleep duration and rhythm[33], cultural and traditional medicine issues and, comprehensively, the quality of life[34-39]. The pre-requisite is that both medical doctor and patient should not be mucking around in search of the magic bullet, and instead try to take seriously and with a strategy the road of lasting lifestyle change.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that 67% of overweight and 94% of obese individuals have NAFLD . Although NAFLD is highly prevalent in the general population, its progressive subtype of nonalcoholic steatohepatitis (NASH) is more clinically relevant . In the United States, an estimated 1.5%‐6.45% of the general population has NASH .…”
Section: Clinical Burden Of Nafldmentioning
confidence: 99%
“…Outcomes frequently measured in studies of patients with chronic diseases such as nonalcoholic fatty liver disease (NAFLD) include morbidity and mortality . Since these outcomes are difficult to measure in clinical trials, investigators rely on histologic, radiologic or other biomakers as surrogates of clinical outcomes . However, assessments of the burden of NAFLD that are limited only to these clinical outcomes do not fully capture the impact of this disease on patients and society .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation